2017
DOI: 10.1002/mp.12358
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of a direct conversion amorphous selenium detector with thicker conversion layer for dual‐energy contrast‐enhanced breast imaging

Abstract: Increasing the a-Se thickness in direct conversion flat-panel imagers results in better performance for dual-energy contrast-enhanced breast imaging. The reduction in spatial resolution due to oblique entry of x-rays is appreciable in the most extreme clinically relevant cases, but may not profoundly affect reconstructed images due to the algorithms and filters employed. Degradation to projection domain spatial resolution is thus outweighed by the improvement in detective quantum efficiency for high-energy x-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…We show that the MTF is degraded by oblique incidence. This result is consistent with previous works on both direct‐ and indirect‐converting detectors . The MTF degradation is most pronounced along the ray incidence direction.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We show that the MTF is degraded by oblique incidence. This result is consistent with previous works on both direct‐ and indirect‐converting detectors . The MTF degradation is most pronounced along the ray incidence direction.…”
Section: Discussionsupporting
confidence: 92%
“…With this approach, we find that the NPS is white. Previous work has demonstrated that, at low energy, the NPS is effectively white . However, in high‐energy applications, it has been shown that the NPS exhibits more pronounced dependency on frequency .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations